Standards to assure quality in nursing research - Zeelie, S C; Bornman, J E; Botes, A C (Curationis (Pretoria), 2003)
The focus of this article is quality assurance in nursing research. Due to well established problems regarding the education of nursing research and increasing pressure to take responsibility for the quality of all educational activities, departments of nursing are obliged to initiate actions to assure quality in nursing research. A nursing department functions within a well-defined external context. The external context comprises of various aspects such as role player expectations and current educational and professional legislation. Standards are the basic components of any quality assurance system (Booyens, 1996:305). Standards give direction to the practitioner and must be compiled within the context of the country's cultural, philosophical and ethical value systems, as well as its social economic and political development. The premise of the study was that if the education of nursing research, indeed the total management of nursing research within the department, is subjected to quality assurance, the outcome of the in terms of nursing research will be positive. The research objective addressed in the study was to formulate and validate standards against which quality in nursing research in a nursing department can be judged. Muller's phases of standard formulation were used as the methodological basis for the study. Optimal, specific standards were formulated using a deductive process and validated by implementing the standards in a department of nursing.